Rapid detection of the bacterial biomarker pyocyanin in artificial sputum using a SERS-active silicon nanowire matrix covered by bimetallic noble metal nanoparticles - Zukovskaja, Olga; Agafilushkina, Svetlana; Sivakov, Vladimir; Weber, Karina; Cialla-May, Dana; Osminkina, Liubov; Popp, Jürgen (Talanta, 2019)
Early stage detection of Pseudomonas infections is life-saving, especially in the case of patients with cystic fibrosis. Pyocyanin (PYO) is a specific metabolite of the Pseudomonas aeruginosa bacteria, and detection of it directly in the sputum can significantly reduce the diagnosis time of the infection. In the present study, aiming to achieve this goal, a simple and cost-effective surface-enhanced Raman spectroscopy (SERS) detection platform was proposed. For this, a silicon nanowire (SiNW) matrix, produced by metal-assisted chemical etching of silicon substrates was variously modified by noble metal (silver and gold) nanoparticles (NPs) and tested for the detection of the metabolite PYO in the complex matrix of artificial sputum. We found the SERS substrate with Ag NPs on the bottom of SiNWs and deposited bimetallic Ag/Au NPs on the top of them the best suited for the sensitive detection of PYO. The investigated plasmonic substrate showed good point-to-point and batch-to-batch signal reproducibility and allowed for the detection of PYO in artificial sputum down to 6.25 μM, which is the required sensitivity for clinical applications.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Metabolite; Pseudomonas aeruginosa; Pyocyanin; Silicon nanowires (SiNWs); Sputum; Surface enhanced Raman spectroscopy (SERS)